2015
DOI: 10.1186/s13071-015-1006-z
|View full text |Cite
|
Sign up to set email alerts
|

ANISERP: a new serpin from the parasite Anisakis simplex

Abstract: BackgroundSerine proteinase inhibitors (serpins) finely regulate serine proteinase activity via a suicide substrate-like inhibitory mechanism. In parasitic nematodes, some serpins interact with host physiological processes; however, little is known about these essential molecules in Anisakis. This article reports the gene sequencing, cloning, expression and preliminary biochemical and bioinformatically-based structural characterization of a new Anisakis serpin (ANISERP).MethodsThe full AniSerp gene was cloned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Screening of potential target mammalian serine proteinases revealed that Bm-SPN-2 inhibits human neutrophil-derived proteinases cathepsin G and elastase (Zang et al 1999). Similarly, the serpin Anisakis simplex serpin (ANISERP) also inhibits cathepsin G, as well as the human blood clotting serine protease thrombin and the digestive serine protease trypsin (Valdivieso et al 2015). In S. ratti, and S. stercoralis there are 12 and 10 genes, respectively, encoding serpins belonging to the trypsin-inhibitor protein family which are significantly upregulated in the parasitic female transcriptome when compared to the free-living female transcriptome.…”
Section: Protein Families With a Putative Role In Parasitismmentioning
confidence: 99%
“…Screening of potential target mammalian serine proteinases revealed that Bm-SPN-2 inhibits human neutrophil-derived proteinases cathepsin G and elastase (Zang et al 1999). Similarly, the serpin Anisakis simplex serpin (ANISERP) also inhibits cathepsin G, as well as the human blood clotting serine protease thrombin and the digestive serine protease trypsin (Valdivieso et al 2015). In S. ratti, and S. stercoralis there are 12 and 10 genes, respectively, encoding serpins belonging to the trypsin-inhibitor protein family which are significantly upregulated in the parasitic female transcriptome when compared to the free-living female transcriptome.…”
Section: Protein Families With a Putative Role In Parasitismmentioning
confidence: 99%
“…Schistosome serpins identified in the blood fluke Schistosoma mansoni are involved in both post-translational regulation of schistosome-derived proteases, as well as in parasite defense mechanisms against the action of host proteases [ 20 ]. In nematodes, serpins interact with endogenous parasite proteinases, counteract the digestion by host proteinases, inhibit the host immune response, or even act as immunomodulators [ 21 , 22 ]. Proteases and their inhibitors have been reported as important factors for invasion and immune evasion of parasites [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In one such example of gene family expansion, serpins (serine proteases) play an important role in parasitic organisms, like defense against host proteases in Schistosoma mansoni and acting as immunomodulators and inhibit host immune responses in nematodes (Maizels et al, 2001; Valdivieso et al, 2015). Recently, a study analyzed the expression-profiles of M. cerebralis serpins and proposed that they represent good targets for inactivating the parasite at an early stage in the fish host (Eszterbauer et al, 2021).…”
Section: Discussionmentioning
confidence: 99%